On the Existence of Global Oscillation Waves for a Class of 3x3 Semilinear Hyperbolic Equations (Journal of Partial Differential Equations, 1999)
ln this paper, we prove the global existence of oscillation waves for a class of 3 × 3 semilinear hyperbolic equations by applying the Young measures and two-scale Young measures which are associated with the solution sequence of the system.
Keywords: Young measures; geometric optics; 3-web curvatures